The relationship between debt and output - Yun Jung Kim; Jing Zhang (Federal Reserve Bank of Chicago, 2020)
In this paper we empirically explore the relationship between debt and output in a panel of 72 countries over the period 1970-2014 using a vector autoregression (VAR). We document two puzzling empirical findings that contrast with what is predicted by a standard small open economy model by Aguiar and Gopinath (2007), where debt and output endogenously respond to total factor productivity (TFP) shocks. First, developing countries' debt falls after a positive output shock, while the model predicts a debt expansion. Second, output declines in developed and developing countries after a debt shock, while the model predicts higher output. The relationship between debt and output depends on the sector taking on debt (households, firms, or governments) and the source of financing (domestic versus external) and differs across countries with varying degrees of economic development or different exchange rate regimes.
Keywords: E44; F32; F34; F41; 330; public debt; household debt; firm debt; foreign debt